ANALISIS PERBANDINGAN PREDIKSI KEBERTERIMAAN E-FILING DENGAN E-FORM DALAM PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN 1770/1770S - Nurhayati, Erni; Hidayat, Nur (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
ABSTRACT This study aims to determine the comparison of predictive acceptance of the application of e-filing and e-form. This study uses qualitative methods with a comparative approach to data collection techniques through literature study and field research and interviews. The selection of respondent is done by purposive sampling with the following criteria: (1) taxpayers whose income is from business or free work or employees who are still active in a company, (2) Own NPWP and obliged to report SPT 1770 or 1770 S, (3) Ever reporting his Personal Annual Tax Return either e-filing at least twice and also e-form at least once through the DJP website. Semi-structured interviews were conducted to 10 resource persons. Data analysis is done by reducing data, presenting data and drawing conclusions. There are four aspects analyzed to determine the predictions of acceptance of e-filing and e-form: performance expectancy, effort expectancy, social influences and facilitating conditions. Based on the analysis, the result shows that overall e-filing is still well received compared to e-form. There are still many taxpayers who feel difficulty with the use of e-form in the reporttax return. Keywords: E-filing, E-form, Prediction of Acceptance